The Role of Dhikr in Improving Psychological Well-Being Through Islamic Spirituality Counselling - Winarti, Dwi; Agustia, Zennanta (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2024)
Psychological problems are so complex, encouraging counsellors to be more aware in dealing with them. Issues such as anxiety disorders, stress, and even depression in recent years have shown alarming numbers. In overcoming these problems, there needs to be a solution step that is effective and has a significant impact on the counsellor. Therefore, this study aims to analyse the role of dhikr in Islamic spirituality counselling as an effort to help clients improve psychological well being. The role of dhikr in Islamic spirituality counselling is expected to be an alternative solution in overcoming problems concerning the world of counselling. This research uses a qualitative method with a spiritual counselling approach. The use of this spiritual counselling approach is considered suitable because it raises dhikr as a major component in the counselling process and at the same time is a form of spiritual behaviour used to remember the existence of God. The results obtained are that in Islam, dhikr is generally believed to have the virtue of providing a sense of calmness in the soul, reviving negligence in the heart, being a medium to get closer to Allah, and divine guidance in providing ideal life direction, which ultimately has an effective impact on psychological well being. This shows that dhikr plays a role in psychological well being.